Implementing tools to support evidence-based practice: a survey and brief intervention study of the National Elf Service across Oxford Health NHS Foundation Trust. Issue 2 (31st March 2017) - Atkinson, Lauren Z; Forrest, Alexandra; Marriner, Leah; Geddes, John; Cipriani, Andrea
Abstract : Background: Technology and the internet has enabled rapid access to research but most mental health professionals do not have time to keep up with the vast and growing scientific literature. Secondary information sources, such as the National Elf Service (NES), aim to summarise the most important and up-to-date research to improve mental health professionals' access to information to support evidence-based medicine (EBM). Objective: To explore mental health professionals' attitudes towards evidence-based practice and methods used to keep up-to-date with research. To promote use of a digital evidence-based platform (the National Elf Service), assess its use and explore its potential to impact clinical practice. Methods: Baseline and follow-up surveys were distributed among staff of 5 adult mental health community teams and 2 early intervention services (n=331) in Oxford Health Foundation Trust (OHFT) prior to and following an intervention raising awareness of the National Elf Service. Findings: Of 133 baseline survey responders, the majority of staff reported their clinical practice was informed by evidence, mostly using existing clinical guidelines and online resources. Few had used the National Elf Service. 122 staff members completed the follow-up survey. Postintervention, 42 staff members indicated they had used the National Elf Service (compared with 13 preintervention) and that it had improved access to research. Lack of time was most often the barrier restricting evidence-based practice. Conclusions: Mental health professionals are engaged with EBM and those that used the National Elf Service felt it did, or could have the potential to impact on their clinical practice. Clinical implications: Barriers and challenges to implement EBM more widely suggest targeted efforts should be made to embed evidence-based practice into the working culture.